Expressions of HPV 16-E6 in esophageal carcinoma and it's clinical significance - Zhao, Xing; Sahi, Rajina; Zhao, Yu-Yang; Wang, Jun; Li, Chun- Hui (Asian Journal of Medical Sciences, 2015)
Aim: To explore the association between HPV16-E6 protein and esophageal squamous cell carcinoma. Materials and Methods: SP immunohistochemical method was used to examine the expression of HPV 16-E6 in 50 cases of esophageal squamous cell carcinoma, 10 cases of normal esophageal squamous cell and 10 cases of adjacent tissue. Results: The expressions of HPV 16-E6 was significantly higher in esophageal carcinoma than in normal esophageal mucosa and in adjacent tissue. The expressions of HPV 16-E6 had correlation with invasive depth (P<0.05), but not with patient age, lymph node metastasis, tumor size (P>0.05). Conclusion: HPV 16-E6 can promote the growth and metastasis of esophageal squamous cell carcinoma and can be a prognostic factor of esophageal squamous cell carcinoma. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12537 Asian Journal of Medical Sciences Vol.6(6) 2015 39-42